CREATING ACTIVITIES FOR CONCLUDING THE LESSON - Dexqonova Madinaxon Sherali qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: In this article Closure is the step where you wrap up a lesson plan and help students organize the information in a meaningful context in their minds. This helps students better understand what they have learned and provides a way in which they can apply it to the world around them.